2021
DOI: 10.1038/s41598-021-82861-6
|View full text |Cite
|
Sign up to set email alerts
|

Particle size and cholesterol content of circulating HDL correlate with cardiovascular death in chronic heart failure

Abstract: Evidence regarding any association of HDL-particle (HDL-P) derangements and HDL-cholesterol content with cardiovascular (CV) death in chronic heart failure (HF) is lacking. To investigate the prognostic value of HDL-P size (HDL-Sz) and the number of cholesterol molecules per HDL-P for CV death in HF patients. Outpatient chronic HF patients were enrolled. Baseline HDL-P number, subfractions and HDL-Sz were measured using 1H-NMR spectroscopy. The HDL-C/P ratio was calculated as HDL-cholesterol over HDL-P. Endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Four blood lipids—TC, TG, LDL‐C, and HDL‐C—are important indicators used to reveal changes in blood lipids (Chen et al, 2021 ). Earlier studies showed that HDL‐C levels negatively correlate with carotid atherosclerosis progression (Hedayatnia et al, 2020 ; Teis et al, 2021 ), while higher LDL‐C levels and lower HDL‐C levels might correlate with cardiovascular diseases (CVDs) such as stroke (Zhang, Wei, et al, 2020 ). This LDL‐C/HDL‐C ratio was proved to be more valuable than any single lipid component—especially LDL‐C—to predict CVDs risk (Hedayatnia et al, 2020 ; Zhang, Wei, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four blood lipids—TC, TG, LDL‐C, and HDL‐C—are important indicators used to reveal changes in blood lipids (Chen et al, 2021 ). Earlier studies showed that HDL‐C levels negatively correlate with carotid atherosclerosis progression (Hedayatnia et al, 2020 ; Teis et al, 2021 ), while higher LDL‐C levels and lower HDL‐C levels might correlate with cardiovascular diseases (CVDs) such as stroke (Zhang, Wei, et al, 2020 ). This LDL‐C/HDL‐C ratio was proved to be more valuable than any single lipid component—especially LDL‐C—to predict CVDs risk (Hedayatnia et al, 2020 ; Zhang, Wei, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods are available for HDL separation, which are used with varying frequency in studies (gel electrophoresis 49 , nuclear magnetic resonance 50 , and ion mobility 51 ). They are based on different physicochemical characteristics of the HDL molecules and separate the particles according to size, charge, density, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a positive association between HDL particle size, as well as HDL cholesterol content (calculated as HDL-C/HDL-p ratio), and cardiovascular death in CHF patients [ 44 ]. In the present study, univariable Cox regression analysis revealed a significant positive association of the HDL-C/HDL-apoA-II ratio (HR 1.37 per 1 SD increase, 95% CI 1.15–1.62, p < 0.001), but not the HDL-C/apoA-I ratio (HR 1.16 per 1 SD increase, 95% CI 0.96–1.41, p = 0.134), with 1-year mortality.…”
Section: Discussionmentioning
confidence: 99%